A matter of will : a novel - Mitzner, Adam (Thomas & Mercer, 2019)
After Wall Street broker Will Matthews wins the business of mysterious Sam Abaddon, he is catapulted into the world of money and luxury, but when Will witnesses a shocking act of violence, his charmed existence is revealed to be a waking nightmare.